IMPLEMENTASI KEBIJAKAN KEPENDUDUKAN (STUDI KASUS PERATURAN DAERAH NOMOR 2 TAHUN 2012 TENTANG RETRIBUSI PENGGANTIAN BIAYA CETAK KARTU TANDA PENDUDUK DAN AKTE CATATAN SIPIL TAHUN 2013) - Febrina, Tria; Ridwan, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The final conclusion is that communication in implementing local regulations No. 02 of 2012 on Print Cost Recovery Levy Identity Card And Deeds Registry runs as expected where the communication goes smoothly to the public good it komunikasilangsung or indirect communication so many people who know about the existence of regulation of this area . Source - the resources to implement local regulations No. 02 of 2012 on Print Cost Recovery Levy Identity Card And Deeds Registry has been fulfilled because in addition to human resources , the government is also preparing dna supporting infrastructure facilities in the implementation of this regulation . Position or attitude in implementing local regulations No. 02 of 2012 on Print Cost Recovery Levy Identity Card And Deeds Registry is considered not run as expected because of the attitude of the apparatus that implements this rule is not everything can be accepted by society . Bureaucratic structures in implementing local regulations No. 02 of 2012 on Print Cost Recovery Levy Identity Card And Deeds Registry rated highly convoluted so many people are confused and feel fatigue in obtaining citizenship documents .Keywords : Implementation , Policy , e - KTP